PENGGUNAAN ALIH KODE DALAM PERCAKAPAN PADA JARINGAN WHATSAPP OLEH MAHASISWA KNB YANG BERKULIAH DI UNIVERSITAS SEBELAS MARET - Khodiyo Thesa; Nababan Nababan; Sri Marmanto (Prasasti: Journal of Linguistics)
The aims of this research are (1) to find the types of code switching that used in what’sapp conversation by KNB students of Sebelas Maret University (2) to describe the factors of code switching by KNB students of Sebelas Maret University (3) to describe the functions of code switching by KNB students of Sebelas Maret University.